Technological developments in the Ottoman navy during the reign of Selim III - Zorlu, Tuncay. (Thesis (Ph.D.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2004., 2004)
The reign of Selim III witnessed technological novelties in the Ottoman navy. Thanks to the access to ample sources for naval construction and wisely navigated channels of information, the systematic construction of new types of sailing warships was adopted in this period. One of the striking breakthroughs of the period was the adoption of copper sheathing for the hulls and bottoms of Ottoman naval ships, from 1207/1792-93 onwards. The construction of the first dry-dock in the Golden Horn was another important development in the period. Furthermore, at the beginning of the nineteenth century the first negotiations with Great Britain regarding the purchase of a steam engine, which the Ottoman authorities intended to use in emptying the dry-dock were initiated. Among other significant technological developments were the construction of an anchor house (lengerhâne); the building of a measuring house (endâzehâne), the adoption of new mast machines, fire conduits, a new ship launching method; the beginning of the keeping of navigational log books; and the introduction of a new kitchen and provisioning system. While, foreign missions, especially French, Swedish and British ones, played important roles in training Ottoman shipbuilders and contributed to the modernisation of the Ottoman naval technology with services they rendered in the shipbuilding sector and naval warfare, they constituted the first instances of technological dependence of the Ottoman State on Europe in the long run.
Keywords: Warships -- Turkey -- History.